A Simple Preparation Method for Phytochromobilin1. (May 2017) - Lu, Lu; Zhao, Bao‐Qing; Miao, Dan; Ding, Wen‐Long; Zhou, Ming; Scheer, Hugo; Zhao, Kai‐Hong
Abstract: Phytochromobilin (PΦB), the chromophore of plant phytochromes, is difficult to isolate because phytochromes occur at very low concentrations in plants. It is, therefore, frequently replaced in plant phytochrome studies by phycocyanobilin, which is abundant in cyanobacteria. PΦB is also an attractive chromophore for far‐red emitting chromoproteins. In this work, we design and optimize a simple method to efficiently isolate useful quantities of PΦB: The chromophore is generated in Escherichia coli and transiently bound to a tailored chromophore‐binding domain of ApcE2, the apo‐protein of a core‐membrane linker, from which it can subsequently be released. The ease and effectiveness of this method hinges not only on the enhanced biosynthesis of PΦB in the presence of the ApcE2 construct from Synechococcus sp. PCC7335, but also on the noncovalent binding of the pigment to its apo‐protein. The isolated PΦB was successfully incorporated into phytochrome‐related assemblies, and furthermore, the noncovalently bound PΦB could be transferred directly from the ApcE2 construct to the apo‐proteins of phytochromes, cyanobacteriochromes and phycobiliproteins, without loss of relevant biological activity. Abstract : Phytochromobilin (PΦB), the chromophore of plant phytochromes, is difficult to isolate because phytochromes occur at very low concentrations in plants. In Escherichia coli, oxygenation of heme catalyzed by heme oxygenase (HO1) and subsequent reduction catalyzed by ferredoxin‐dependent phytochromobilin reductase (HY2) generates phytochromobilin. Because biosynthesis of phytochromobilin is enhanced in the presence of a tailored construct of ApcE2, the apo‐protein of a core–membrane linker from Synechococcus sp. PCC7335, and phytochromobilin is only noncovalently bound to ApcE2, phytochromobilin can be easily released under denaturation in the presence of 8 m urea, and phytochromobilin is conveniently and efficiently isolated by present method.